Second (and Third) Thoughts on Adaptive Management and Thinking and Working Politically - and Green, Duncan (2022)
Self-Critical reflections on AM and TWP. Linking it with The Hype Cycle - "it feels like we are heading downward to the ‘trough of disillusionment’ form the initial peak of ‘inflated expectations’, but we will bounce back to something more sustained, that becomes a permanent feature of the aid landscape".